Political Culture and Heritage Education: Law 10.639/03 - Possible contributions - Santana, Nara Maria de; Aureliano, Niara Oiara da Silva (Faculdade de Educação/Universidade Estadual de Campinas, 2020)
The work presented here aims to analyze Political Culture in Brazil, the influence of this culture in the development of Law 10.639-03 and in Heritage Education, which concerns the assets identified as Afro and Afro-Brazilian Culture. To this end, the history of Heritage policies created in the country throughout the 20th century will be researched, with an emphasis on the 80s and 90s and focusing these efforts on the spatial profile of the city of Rio de Janeiro; law 10.639 \ 03, its brief history and proposal and Heritage Education and its possible contributions to the legislation and to Political Culture. The methodology will be based on bibliographic sources that discuss the meaning of Political Culture and Heritage Education and  with a secondary source. We highlight, the use of "rational and orderly procedure", with the evaluation of the bibliographic and documentary material, the measurement of data and a analysis, in order to achieve the objectives established. Keywords: Political Culture. Heritage Education. Law 10.639 \ 03.